Mathematical handbook for scientists and engineers : definitions, theorems, and formulas for reference and review - Korn, Granino A. 1922-2013 (Dover Publications, 2000)
A reliable source of definitions, theorems, and formulas, this authoritative handbook provides convenient access to information from every area of mathematics.